1995
DOI: 10.1172/jci117776
|View full text |Cite
|
Sign up to set email alerts
|

Modified low density lipoprotein and its constituents augment cytokine-activated vascular cell adhesion molecule-1 gene expression in human vascular endothelial cells.

Abstract: IntroductionEarly features in the pathogenesis of atherosclerosis include accumulation of oxidized LDL (oxLDL) and endothelial expression of the vascular adhesion molecule VCAM-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
208
0
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(222 citation statements)
references
References 43 publications
5
208
0
9
Order By: Relevance
“…In contrast to previous studies (15,24), LPC does not contribute to the effects of oxLDL. This is consistent with results showing that effects of oxLDL are not necessarily mediated by LPC (25). Optimal treatment with LPC requires binding to BSA (24), causing differences in effectiveness.…”
Section: Monocyte Adhesion To Oxidized Low Density Lipoprotein-stimulsupporting
confidence: 91%
“…In contrast to previous studies (15,24), LPC does not contribute to the effects of oxLDL. This is consistent with results showing that effects of oxLDL are not necessarily mediated by LPC (25). Optimal treatment with LPC requires binding to BSA (24), causing differences in effectiveness.…”
Section: Monocyte Adhesion To Oxidized Low Density Lipoprotein-stimulsupporting
confidence: 91%
“…Glycaemic control in NIDDM patients could therefore be related to E-selectin plasma concentration, through its effect on the parameters correlated to oxidative stress. In this context, exciting recent findings indicated that oxidized LDL and plasma hydroperoxides can affect the expression of adhesion molecules on endothelial cells in vitro [26,27]. Additional evidence that the adhesion molecule expression on endothelial cells is an oxidative stress-responsive event comes from the inhibitory effects of various structural antioxidants in response to many different stimuli [27].…”
Section: Discussionmentioning
confidence: 99%
“…An enhanced oxidative stress, i. e. increased levels of plasma hydroperoxides, has actually been observed in NIDDM [20][21][22][23][24]. The augmented generation of free radicals could also result in oxidative damage of LDL, the known potentially atherogenic properties of oxidized LDL including monocyte recruitment [25] and modulation of expression of adhesion molecules [26,27]. Enhanced susceptibility of LDL to oxidation has recently been reported in diabetic patients [24,28,29].…”
mentioning
confidence: 99%
“…The leading hypothesis for atherogenesis is that it is due to an excessive fibroproliferative response to arterial injury [2]. One scenario for this injury is that lipoprotein is trapped in the arterial intima where it is oxidized, leading to the induction of endothelial adhesion molecules such as VCAM-1 [3]. Via these adhesion molecules, monocytes and T cells enter the arterial wall where the monocytes differentiate into macrophages.…”
Section: Introductionmentioning
confidence: 99%